Fermentable soluble fibres spare amino acids in healthy dogs fed a low-protein diet. Issue 1 (December 2016) - Wambacq, Wendy; Rybachuk, Galena; Jeusette, Isabelle; Rochus, Kristel; Wuyts, Brigitte; Fievez, Veerle; Nguyen, Patrick; Hesta, Myriam
Abstract Background Research in cats has shown that increased fermentation-derived propionic acid and its metabolites can be used as alternative substrates for gluconeogenesis, thus sparing amino acids for other purposes. This amino acid sparing effect could be of particular interest in patients with kidney or liver disease, where this could reduce the kidneys'/liver's burden of N-waste removal. Since dogs are known to have a different metabolism than the obligatory carnivorous cat, the main objective of this study was to assess the possibility of altering amino acid metabolism through intestinal fermentation in healthy dogs. This was studied by supplementing a low-protein diet with fermentable fibres, hereby providing an initial model for future studies in dogs suffering from renal/liver disease. Results Eight healthy dogs were randomly assigned to one of two treatment groups: sugar beet pulp and guar gum mix (SF: soluble fibre, estimated to mainly stimulate propionic acid production) or cellulose (IF: insoluble fibre). Treatments were incorporated into a low-protein (17 %) extruded dry diet in amounts to obtain similar total dietary fibre (TDF) contents for both diets (9.4 % and 8.2 % for the SF and IF diet, respectively) and were tested in a 4-week crossover feeding trial. Apparent faecal nitrogen digestibility and post-prandial fermentation metabolites in faeces and plasma were evaluated. Dogs fed the SF diet showed significantly higher faecal excretion of acetic and propionic acid, resulting in a higher total SCFA excretion compared to IF. SF affected the three to six-hour postprandial plasma acylcarnitine profile by significantly increasing AUC of acetyl-, propionyl-, butyryl- + isobutyryl-, 3-OH-butyryl-, 3-OH-isovaleryl- and malonyl-L-carnitine. Moreover, the amino acid plasma profile at that time was modified as leucine + isoleucine concentrations were significantly increased by SF, and a similar trend for phenylalanine and tyrosine's AUC was found. Conclusion These results indicate that guar gum and sugar beet pulp supplementation diminishes postprandial use of amino acids favoring instead the use of short-chain fatty acids as substrate for the tricarboxylic acid (TCA) cycle. Further research is warranted to investigate the amino acid sparing effect of fermentable fibres in dogs with kidney/liver disease.